The Student's Propensity in the Usage of Interpreting Skill and Processes in English-Indonesian Interpreting Practice in Online Learning - Ida Lisdawati; Ula Nisa El Fauziah (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2021)
The objective of this research was to figure out the students’ dominant interpreting skills and process during the interpreting practice to hone their interpreting ability in English-Indonesia Interpreting class. This research was conducted to the last years university students and took 20 students as sample that taken by simple random sampling. This research employed the descriptive method. The instruments of this research were oral test and monitoring guide for observing interpreter practice. The result of this research located that the students’ oral test score was 6. It pointed out that students’ interpreting skill in fair level. Meanwhile, the average score of their decoding skill was 24. It showed that their decoding skill was at the very poor level. The student’s accuracy average score was 2,1. It pointed that they got the needed improvement level, and the average score of the student’s recording skill is 0.3. It means that they are in the unacceptable level in interpreting practice. The conclusion of this research is the students still having the lack of interpreting skill and process. They tend inconsistent in interpreting process.